Analysis Of The Effectiveness Of Using Instructional Videos In The Classroom At Mts Salafiyyah Syafi'iyyah Tebuireng - Bagas Setiawan; Sulton; Hasanatun Nadia; Rofiatul Hosna (Tarbiyah bil Qalam : Jurnal Pendidikan Agama dan Sains, 2026)
This study investigates the effectiveness of using educational videos in classroom instruction at MTs Salafiyyah Syafi’iyyah Tebuireng, a school that integrates both general and religious education. The research is motivated by ongoing challenges in students’ learning, which are often linked to ineffective teaching strategies, limited learning resources, and low levels of student motivation. Educational videos are considered a promising instructional medium because they combine visual and auditory elements, making complex concepts easier to understand and increasing student engagement. This study examines how the use of such videos impacts student participation, comprehension, and overall classroom dynamics, while also fostering a more interactive and stimulating learning environment. Furthermore, the research explores several critical factors that influence the effectiveness of video-based instruction, including the relevance of the content, the quality of the media, the teacher’s ability to facilitate learning, and the school’s readiness to implement technology. As a pesantren-based institution, MTs Salafiyyah Syafi’iyyah faces both unique challenges and opportunities in integrating modern educational technologies. The findings of this study aim to provide practical insights into how video-supported learning can enhance teaching quality and improve educational outcomes for students in this distinctive learning context.